2022
DOI: 10.3390/children9111708
|View full text |Cite
|
Sign up to set email alerts
|

Association between History of Prolonged Exclusive Breast-Feeding and the Lung Function Indices in Childhood

Abstract: Although the propitious effects of breastfeeding on children’s health are indisputable, the impact of exclusive breastfeeding on the lung function later in life remains controversial. Our objective was to explore the possible associations between breastfeeding and the lung function of children who were exclusively breastfed for an extensive period of time. This was a cross-sectional study of children who were exclusively breastfed for more than 12 months. Demographics and anthropometric data were collected; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…8 Low coverage of exclusive breastfeeding is a risk factor for various nutritional and health problems in children. [23][24][25] The United Nations Children'sFund(UNICEF) states that breast milk can save infants' lives, especially in developing countries, due to the high prevalence of diarrhea and acute respiratory infections in developing countries. 9 Breast milk is the best source of nutrients that can improve the health of mothers and children.…”
Section: Discussionmentioning
confidence: 99%
“…8 Low coverage of exclusive breastfeeding is a risk factor for various nutritional and health problems in children. [23][24][25] The United Nations Children'sFund(UNICEF) states that breast milk can save infants' lives, especially in developing countries, due to the high prevalence of diarrhea and acute respiratory infections in developing countries. 9 Breast milk is the best source of nutrients that can improve the health of mothers and children.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from observational studies suggests that breastfeeding minimizes the pulmonary sequelae of respiratory infections, improves lung function in school-age children, and also protects lung function in children who are exposed to high levels of air pollution and passive smoking [ 23 , 25 , 26 ]. It suggests that breastfeeding appears to counteract the effects of environmental detrimental influences on lung development [ 27 ]. A birth cohort study of healthy infants found protective causal effects of exclusive breastfeeding on the risk of developing a lower respiratory tract infection in infancy and asthma and allergic rhinitis in childhood, which were mediated through interactions on the gut microbiota [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A birth cohort study of healthy infants found protective causal effects of exclusive breastfeeding on the risk of developing a lower respiratory tract infection in infancy and asthma and allergic rhinitis in childhood, which were mediated through interactions on the gut microbiota [ 28 ]. However, there is controversy in many studies in this field as to whether the duration of breastfeeding is associated with asthma [ 23 , 24 , 25 , 26 , 27 , 28 ]. In this study, we examined whether the child was breastfed and the duration of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research has indicated that breastfeeding can help protect lung function in individuals who are exposed to high levels of air pollution [ 34 ], including passive smoking [ 35 ]. These findings suggest that breastfeeding might mitigate the negative impacts of environmental factors on the developing lungs [ 36 ].…”
Section: Breastfeeding and The Lung Functionmentioning
confidence: 99%